2021
DOI: 10.1039/d0fo03345f
|View full text |Cite
|
Sign up to set email alerts
|

Antrodin A fromAntrodia camphoratamodulates the gut microbiome and liver metabolome in mice exposed to acute alcohol intake

Abstract: This study aimed to investigate the protective effect of Antrodin A (AdA) from Antrodia camphorata (A. camphorata) mycelium on alcohol-induced gut microbiota and liver metabolomic disorders. In acute alcoholic liver...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 51 publications
8
43
0
Order By: Relevance
“…The applied 16S rRNA gene amplicon sequencing methods does, however, not make it possible to investigate this finding at a deeper taxonomic resolution. We observed that HFD mice have increased Dubosiella , which has been previously described in dysbiosis conditions such as GDM and obesity ( Bai et al, 2019 ; Li et al, 2020 ; Sheng et al, 2020 ; Qiu and Macchietto, 2021 ; Yi et al, 2021 ). Positive correlations of Dubosiella with FBG, FINS, and TC demonstrated that these bacteria may promote the glycolipid metabolism disorders, which could be reversed by ITF treatment.…”
Section: Discussionsupporting
confidence: 69%
“…The applied 16S rRNA gene amplicon sequencing methods does, however, not make it possible to investigate this finding at a deeper taxonomic resolution. We observed that HFD mice have increased Dubosiella , which has been previously described in dysbiosis conditions such as GDM and obesity ( Bai et al, 2019 ; Li et al, 2020 ; Sheng et al, 2020 ; Qiu and Macchietto, 2021 ; Yi et al, 2021 ). Positive correlations of Dubosiella with FBG, FINS, and TC demonstrated that these bacteria may promote the glycolipid metabolism disorders, which could be reversed by ITF treatment.…”
Section: Discussionsupporting
confidence: 69%
“…It was shown that ascorbate and aldarate metabolism could protect the liver from alcoholic hepatitis. [ 57,58 ] Based on the above, we presume that VTE may ameliorate liver damage via affecting the metabolic activity of gut microbiota in ALI mice. Further, the correlation analysis suggests that the above changed intestinal flora were correlated with the abnormal physiological parameters and liver injury‐related biomarkers (Figure 6C).…”
Section: Discussionmentioning
confidence: 99%
“…51–55 The Lachnospiraceae_NK4A136_group , Bacteroides , and Odoribacter have a higher abundance in cancer patients, promoting the occurrence of cancer. 56–58 A high-fat diet can increase the abundance of Dubosiella and Odoribacter , leading to intestinal flora disorder. 59,60 Moreover, the abundance of Akkermansia was down-regulated in the TPD group, and Akkermansia was positively correlated with type 2 diabetes and promoted colitis and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%